Archival Film Curatorship Early and Silent Cinema from Analog to Digital - Ingravalle, Grazia (Framing Film, 2024)
Archival Film Curatorship is the first book-length study that investigates film archives at the intersection of institutional histories, early and silent film historiography, and archival curatorship. It examines three institutions at the forefront of experimentation with film exhibition and curatorship. The Eye Film Museum in Amsterdam, the George Eastman Museum in Rochester, NY, and the National Fairground and Circus Archive in Sheffield, UK serve as exemplary sites of historical mediation between early and silent cinema and the digital age. A range of elements, from preservation protocols to technologies of display and from museum architectures to curatorial discourses in blogs, catalogs, and interviews, shape what the author innovatively theorizes as the archive's hermeneutic dispositif. Archival Film Curatorship offers film and preservation scholars a unique take on the shifting definitions, histories, and uses of the medium of film by those tasked with preserving and presenting it to new digital-age audiences.